Features of clinical course of chronic hepatitis in children with oenological diseases - Nezgoda, I. I.; Moroz, L. V.; Singh, S.; Singh, O. O. (Journal of Education, Health and Sport, 2017)
The article presents the results of the study including 187 children with chronic hepatitis aged from 3 to 18 years. All were under dispensary observation at the Regional Pediatric Infectious Diseases Hospital, Vinnytsia, Ukraine, till April 30, 2017. The features of clinical symptoms in 82 children with chronic hepatitis B and C with oncological diseases were also defined. It was determined that among the dispensary observation group of children, 70 (37,4%) patients were with chronic hepatitis B (HBV), 99 (53%) – chronic hepatitis C (CHC), mіх - hepatitis (B + C) were diagnosed in 9,6% (18) patients. In 82 children (43,8%), chronic hepatitis was acquired on the background of the existing oncological disease. In general, hepatitis developed in children with acute lymphoblastic leukemia 61% (50 patients). Most of the children were with age 9-18 (53,4%). Among the patients of CHB 32 (45,7%) were with oncohematological diseases. While in children with CHC such patients were 35 (35,3%), in the group of mіх - hepatitis (B + C) – 83,3% (15 patients) were with oncohematological diseases. Hepatitis in patients with cancer develops in a primary - chronic form (91,5%) with minimal clinical signs of the disease, 8,5% of patients develop manifest disease pattern, 6,09% of patients the phenomenon of self - elimination of the virus were observed. Chronic hepatitis was with normal bilirubin count and fractions. In 1/3 of the patients, the liver enzymes were normal, despite of this all patients had a high viral load. Deep fibrosis changes in liver were found in the children of older age group and the degree of fibrosis increases with the increase in age.